Legal Force of Information Technology-Based Money Lending Agreements - Yambo, Dhaly Grendi; Marsuni, Lauddin; Aswari, Aan (Faculty of Law, Universitas Muslim Indonesia, 2025)
This study aims to determine the legal validity of information technology-based loan agreements. The research method used is normative legal research, which utilizes secondary data sources. These sources include the opinions of experts or specialists who study books, journals, and literature on the legal basis of contracts and laws and regulations. The research findings indicate that Information Technology-Based Lending Services (Fintech Lending) are an innovation in the financial sector that enables online lending and borrowing transactions using electronic systems. Online loan agreements are regulated by Financial Services Authority Regulation Number 10/POJK.05/2022. These agreements are legally valid and enforceable as long as they meet the legal requirements as stipulated in Article 1320 of the Civil Code, namely agreement, capacity, a specific matter, and a lawful cause. Dispute resolution in information technology-based loan agreements in the event of default can be carried out through litigation or non-litigation. Litigation is commonly referred to as the path taken in court, while non-litigation is through Alternative Dispute Resolution Institutions (LAPS), which include mediation, arbitration, and binding opinions. This research recommends educating users about the terms and conditions of agreements, focusing on legal validity and certainty, and strengthening regulations on personal data security and dispute resolution mechanisms.